Fast Li Storage in MoS2‐Graphene‐Carbon Nanotube Nanocomposites: Advantageous Functional Integration of 0D, 1D, and 2D Nanostructures. Issue 4 (18th October 2014) - Zhu, Changbao; Mu, Xiaoke; van Aken, Peter A.; Maier, Joachim; Yu, Yan
<x xml:space="preserve">Abstract</x> A 3D porous composite consisting of nano‐0D MoS2, nano‐1D carbon nanotubes (CNTs), and nano‐2D graphene is successful prepared using an electrostatic spray deposition (ESD) technique. Depending on the preparation procedure either nanodots of amorphous MoS2 (0.5–5 nm) or nanocrystalline few‐layered MoS2 (5–10 nm) bonded to graphene‐carbon nanotubes backbone are obtained. These functionalized carbon nanotubes adhere to a porous graphene‐based network. Such composites can be directly deposited on the current collectors without any binder or conductive additives to assemble a battery that shows superior rate performance and cycling stability. For nanodots, nucleation and diffusion issues usually connected with conversion are largely mitigated if not totally nullified. The use of mechanically and diffusionally isolated but electrochemically well connected electroactive nanodots offer an effective solution to render conversion reaction reversible. The use of nano‐1D and nano‐2D carbon structures offer additional electrical and mechanical advantages that are discussed. Furthermore, this technique, which is easily extendable to other electrode materials, seems to be of a great potential, especially for thin‐film batteries, flexible batteries, and future paintable batteries.